Fecal Methylmercury Correlates With Gut Microbiota Taxa in Pacific Walruses (Odobenus rosmarus divergens) - Rothenberg, Sarah E.; Sweitzer, Danielle N.; Rackerby, Bryna R.; Couch, Claire E.; Cohen, Lesley A.; Broughton, Heather M.; Steingass, Sheanna M.; Beechler, Brianna R. (Frontiers in Microbiology, 2021)
Objectives: Methylmercury metabolism was investigated in Pacific walruses (Odobenus rosmarus divergens), from St. Lawrence Island, Alaska, USA. Methods: Total mercury and methylmercury concentrations were measured in fecal samples and paired colon samples (n=16 walruses). Gut microbiota composition and diversity were determined using 16S rRNA gene sequencing. Associations between fecal and colon mercury and the 24 most prevalent gut microbiota taxa were investigated using linear models. Results: In fecal samples, the median values for total mercury, methylmercury, and %methylmercury (of total mercury) were 200 ng/g, 4.7 ng/g, and 2.5%, respectively, while in colon samples, the median values for the same parameters were 28 ng/g, 7.8 ng/g, and 26%, respectively. In fecal samples, methylmercury was negatively correlated with one Bacteroides genus, while members of the Oscillospirales order were positively correlated with both methylmercury and %methylmercury (of total mercury). In colon samples, %methylmercury (of total mercury) was negatively correlated with members of two genera, Romboutsia and Paeniclostridium. Conclusions: Median %methylmercury (of total mercury) was ten times higher in the colon, compared to fecal samples, suggesting methylmercury was able to pass through the colon into systemic circulation. Fecal total mercury and/or methylmercury concentrations in walruses were comparable to some human studies, despite differences in the seafood consumption rates, suggesting that walruses excreted less mercury. There are no members (at this time) of the Oscillospirales order, which are known to contain the genes to methylate mercury, suggesting the source of methylmercury in the gut was from diet, and not in vivo methylation.